Versatile tactics of elite ski cross-country skiers in simultaneous-start and pursuit races - Novikova, N. B.; Kotelevskaya, N. B.; Zakharov, G. G. (Theory and Practice of Physical Culture, 2018)
The study gives an overview of the winter sports research projects of Saint Petersburg Scientific Research Institute of Physical Culture (SPSRIPC) with a special emphasis on the versatile tactics of the elite cross-country skiers in simultaneous-start and pursuit ski races for the competitive performance improvement purposes. Objective of the study was to analyze the modern cross-country skiing tactics most efficient in contact races. 30 elite national cross-country skiers were sampled for the study of their competitive performance in 11 events of the 2017-18 World Cup finals. The study profiled the interval speed and speed variation ranges in the events including the simultaneous-start and pursuit races to find the speed sagging trend in the middle-distance section and rate accelerations in the final section. The leading athletes were tested with the highest speed variation range on the middle-distance intervals - from 3.33% to 8.35% in the 15km races to 6.1% to 10.7% in the 30km skiathlon. The leaders` competitive performance was found largely determined by the speed controls on the difficult terrains in the middle to final sections of the distance.